Development of Nano Metal Powders for Ultra-Low Fire MLC Inner Electrodes - Fernando de la Vega; Eynat Mtzner; Erik Khasin; Aharon Naor; Asaf Greenshpan (Active and Passive Electronic Components)
The need to reduce metal content, especially Palladium content in the multi layer ceramic components is driven by two motives. The first is the need to reduce material costs which has become a major issue due to the sharp rise and instability of palladium price. The second motive is the need to build components with ever-growing number of layers, in order to achieve better performance.